SINTESIS OF PERFORMANCE DETERMINING FACTORS AND EMPLOYEE PRODUCTIVITY IN THE MODERN ERA: COMPREHENSIVE LITERATURE STUDY - Fora, Yandri; Saluy, Ahmad Badawi (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study aims to synthesize findings from empirical studies on factors that influence employee performance and productivity in the context of modern organizations in Indonesia and beyond. Employee performance and productivity are crucial elements for the success and sustainability of organizations amidst intense business competition and dynamic changes in the work environment, including adaptation to work models such as Work From Home (WFH). This article uses a qualitative literature study method on articles/journals covering various key variables such as organizational/work culture, work environment, compensation, motivation, job satisfaction, organizational commitment, workload, work discipline, work stress, and work-life balance. The results of the analysis indicate a complex and interrelated relationship between these variables. It is consistently found that a positive organizational culture, intrinsic and extrinsic motivation, and organizational commitment have a significant influence on improving performance and productivity. A conducive work environment and job satisfaction often act as important mediators in this relationship. However, the influence of variables such as compensation, workload, and work discipline show varying results depending on the organizational context and individual characteristics. This study underlines the importance of a holistic and integrated human resource management approach to optimize employee performance and productivity. Practical implications and suggestions for further research are also discussed.